Maize intercropping enriches plant growth-promoting rhizobacteria and promotes both the growth and volatile oil concentration of Atractylodes lancea - Peng, Zheng; Guo, Xiuzhi; Xiang, ZengXu; Liu, Dahui; Yu, Kun; Sun, Kai; Yan, Binbin; Wang, Sheng; Kang, Chuanzhi; Xu, Yang; Wang, Hongyang; Wang, Tielin; et al. (Frontiers in Plant Science, 2022)
In the Atractylodes lancea (A. lancea)-maize intercropping system, maize can promote the growth of A. lancea, but it is unclear whether this constitutes an aboveground or belowground process. In this study, we investigated the mechanisms of the root system interaction between A. lancea and maize using three different barrier conditions: no barrier (AI), nylon barrier (AN), and plastic barrier (AP) systems. The biomass, volatile oil concentration, physicochemical properties of the soil, and rhizosphere microorganisms of the A. lancea plant were determined. The results showed that (1) the A. lancea - maize intercropping system could promote the growth of A. lancea and its accumulation of volatile oils; (2) a comparison of the CK, AI, and AP treatments revealed that it was the above-ground effect of maize specifically that promoted the accumulation of both atractylon and atractylodin within the volatile oils of A. lancea, but inhibited the accumulation of hinesol and β-eudesmol; (3) in comparing the soil physicochemical properties of each treatment group, intercropping maize acidified the root soil of A. lancea, changed its root soil physicochemical properties, and increased the abundance of the acidic rhizosphere microbes of A. lancea at the phylum level; (4) in an analysis of rhizosphere microbial communities of A. lancea under different barrier systems, intercropping was found to promote plant growth-promoting rhizobacteria (PGPR) enrichment, including Streptomyces, Bradyrhizobium, Candidatus Solibacter, Gemmatirosa, and Pseudolabrys, and the biomass of A. lancea was significantly influenced by PGPR.